CORRECT MECHANIC AND TECHNICAL CHARACTERISTICS OF «LAUNCH» AND «PEAK» - MIESHKOV, Yurii; VOYTOVICH, Olga (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article compares the mechanical and technical characteristics of car lifts used at all car service centers. Over the last 20 years, two-post lifts have taken their place and gained popularity, they have overtaken four-post lifts by more than three times, if only because they cost less. Two-post jacks were originally used to check and service oil, tires, etc., but are now widely used for major activities (although four-post jacks are still required for a full MOT). Nevertheless, many experts do not stop reporting the risk of falling vehicles from two-post lifts. There have been known cases over the past five years, when not only the car was damaged during the fall from the lift, but also the workers were seriously injured, and there were also fatal cases. Therefore, the opinion of the inspection department is that any fall of the vehicle from a height carries a high risk and fatal injuries. Manufacturers of medium and premium lifting equipment began to introduce budget models into their lines. They follow the path of structural simplification of models, reduce production costs, use cheaper metals, remove electronic systems, which allows to reduce the cost of equipment. The lift market shows almost no changes in terms of assortment. It is segmented according to the type of lifters – two-post, plunger, scissor, roll-up ditch, four-post, multi-post plunger. When considering the market of lifting equipment, one cannot ignore the Chinese car manufacturers, which occupy a solid share in the overall structure of this product group. “The Chinese equipment market is now clearly divided into two classes – one is represented by cheap and low-quality products, and the other is a segment of equipment of decent quality. There is a clear difference between the two segments that is clear to a professional. When choosing Chinese lifts, customers understand that if they ask for little money for the equipment, it will not last long. There is a lot of such low-quality equipment on the market, and this product generally discredits the entire segment from China.